Association of serum progesterone levels on the transfer day with pregnancy outcomes in hormone replacement frozen-thawed cycles with oral dydrogesterone for strengthened luteal phase support - Huiqun Yin; Hong Jiang; Jie Zhu; Cunli Wang; Zhenyi Cao; Kang Luan; Yan Wu (Elsevier, 2023)
Objective: To investigate the relationship between serum progesterone (P) levels on the day of blastocyst transfer and pregnancy outcomes in frozen-thawed embryo transfer (FET) cycles using hormone replacement therapy (HRT) with oral dydrogesterone for strengthened luteal phase support (LPS). Materials and methods: This was a retrospective study including 1176 FET cycles. All patients received 40 mg of intramuscular (IM) P daily for endometrium transformation plus oral dydrogesterone 10 mg BID from transfer day for strengthened LPS. Pregnancy outcomes were compared between serum P levels on the transfer day ≥10 ng/ml and <10 ng/ml. Furthermore, cycles were divided into 10 groups by deciles of P and ongoing pregnancy rate (OPR) was calculated in each group. Analyses using deciles of serum P were completed to see if these could create further prognostic power. Results: No differences were observed in clinical pregnancy rates (CPRs), OPRs and live birth rates (LBRs) between serum P levels ≥10 ng/ml and <10 ng/ml. Patients with serum P levels <5.65 ng/ml (10th percentile) had a significantly lower OPR (48.31% vs. 58.98%, p = 0.03) and LBR (43.22% vs. 57.75%, p = 0.003) than the rest of the patients. Multivariate logistic regression analysis showed serum P levels on the transfer day were not associated with pregnancy outcomes. Conclusion: Measuring serum P levels on the day of HRT-FET is of clinical importance. Lower serum P levels impact the success of HRT-FET cycles, suggesting that there may be a threshold below which it is difficult to improve pregnancy outcomes via oral dydrogesterone to strengthen LPS.